Hospitalization rates and 30-day all-cause mortality among head and neck cancer patients and survivors with COVID-19. (January 2021) - Hanna, Glenn J.; Rettig, Eleni M.; Park, Jong C.; Varvares, Mark A.; Lorch, Jochen H.; Margalit, Danielle N.; Schoenfeld, Jonathan D.; Tishler, Roy B.; Goguen, Laura A.; Annino, Donald J.; Haddad, Robert I.; Uppaluri, Ravindra
Graphical abstract: Highlights: We note high 30-day all-cause mortality for HNC patients admitted with COVID-19. ICU admission and residing in a LTC facility predicted poor outcomes. Most deaths were in HNC survivors and not in those on active cancer therapy. Abstract: Background: The impact of COVID-19 on patients with cancer is emerging, but data are urgently needed for head and neck cancer (HNC) patients or survivors who are inherently high-risk for severe illness and mortality with SARS-CoV-2 infection. Methods: This multi-institution, academic cohort study collected comprehensive data on clinical risk factors, COVID-19 symptoms and viral testing patterns, information about hospitalization rates, and predictors of survival among HNC patients with active disease or in remission. The primary endpoint was 30-day all-cause mortality from the date of confirmed COVID-19. We performed multivariate analysis to understand the prognostic value of clinical and laboratory parameters on outcomes. Results: Thirty-two patients with COVID-19 and HNC were included. Median age was 70 (range: 38–91) with 38% aged 75+, and 34% resided in long-term care facilities (LTCF). Thirteen (41%) had active cancer, with 6 (19%) on cancer therapy within 4 weeks of COVID-19 diagnosis. New or worsening cough and fatigue were the most commonly reported presenting symptoms. More than 30% required >1 SARS-CoV-2 test before confirming a positive result. Twenty (63%) required hospitalization. At data cutoff, 7 (22%) had died (1 on active cancer treatment), with a 30-day all-cause mortality of 18.9% (95%CI: 11.4–33.6) among all patients, and 71.5% (95%CI: 38.2–92.3) among those requiring intensive care unit (ICU) admission. ICU admission and residing in a LTCF predicted worse outcomes (p < 0.01), while age, gender, and recent treatment did not. Conclusions: We observed high 30-day all-cause mortality among HNC patients with COVID-19, but most were not on active cancer therapy.